The Use of Virtual Twins in the Robotic Yoghurt Mixing Process - Wojciech KACZMAREK; Szymon BORYS; Jarosław PANASIUK; Michał SIWEK (Problemy Mechatroniki)
This paper presents the results of computer simulations related to the selection and optimisation of parameters for a robotic yoghurt mixing process. The authors proposed a station configuration using the RobotStudio environment for off-line robot programming and virtual controller technology and determined the performance of the robotised production line. The main component of the study was a computer simulation of the station based on the Picking PowerPac package and Pick Master 3 program. As a result of the simulations, numerical values were obtained informing about the number of handled and rejected products, filled containers and the times of production cycles of the station.